2007
DOI: 10.1016/j.lpm.2007.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome POEMS

Abstract: The POEMS syndrome combines a constant polyneuropathy (P), organomegaly (O), endocrinopathy (E), monoclonal gammopathy (M) (or other plasma cell disorder) and skin changes (S). Other manifestations may be observed: anasarca, fever, sweating, clubbed fingers, renal damage, arterial obstruction, pulmonary hypertension, thrombocytosis, and polycythemia. Its pathogenesis is not well elucidated but elevated levels of vascular endothelial growth factor (VEGF) appear to characterize it. Consistent plasma cell disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
1
0
3
Order By: Relevance
“…In 2017, Hu et al 19 found mild primary hypothyroidism in 13 of 22 patients with POEMS syndrome (high prevalence of 59%). Furthermore, Soubrier 20 found secondary (central) hypothyroidism in 2 of 10 patients with hypothyroidism and in all 25 patients with POEMS syndrome. The underlying causes of hypothyroidism need to be further elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…In 2017, Hu et al 19 found mild primary hypothyroidism in 13 of 22 patients with POEMS syndrome (high prevalence of 59%). Furthermore, Soubrier 20 found secondary (central) hypothyroidism in 2 of 10 patients with hypothyroidism and in all 25 patients with POEMS syndrome. The underlying causes of hypothyroidism need to be further elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…Soubrier. M a insisté sur le fait que les patients ayant une neuropathie périphérique inexpliquée doivent bénéficier d'une électrophorèse et d'une immunoélectrophorèse à la recherche d'un composant monoclonal orientant vers ce diagnostic pour réduire le retard diagnostique et améliorer la réponse thérapeutique de ces lésions neurologiques [ 7 ]. Le traitement par la thalidomide ou le lénalidomide, prescrits par Tomás et al [ 8 ], ont donné de bons résultats avec diminution du taux de VEGF et de la neuropathie.…”
Section: Discussionunclassified
“…La greffe de moelle serait indiquée dans les formes réfractaires à la corticothérapie, la chimiothérapie et la radiothérapie. Le bévacizumab, anticorps monoclonal anti-VEGF, a amélioré de façon spectaculaire 2 patients mais en a aggravé un autre [ 7 ]. L’évolution fatale chez notre patient serait en rapport avec le retard diagnostique et thérapeutique.…”
Section: Discussionunclassified
“…Les lymphocytes T CD8 + sont au coeur de ce processus, à la fois effecteurs et cibles de l'apoptose, mais également cibles potentielles sur le plan thérapeutique [9]. Soubrier [6] met en lumière le rôle potentiel des cytokines pro-inflammatoires dans la physiopathologie du syndrome POEMS, en particulier du Vascular Endothelial Growth Factor (VEGF) dont l'augmentation des taux semble caractéristique du syndrome [10]. Le rôle du virus humain Herpes 8 dans le cadre du syndrome POEMS, notamment de sa forme histologique de type Castleman, reste débattu.…”
unclassified